2006
DOI: 10.1002/jcop.20124
|View full text |Cite
|
Sign up to set email alerts
|

A model for the influence of mentoring relationships on youth development

Abstract: Anecdotal reports of the protective qualities of mentoring relationships for youth are corroborated by a growing body of research. However, few researchers have explored the processes by which mentors influence developmental outcomes. In this article, we present a conceptual model of the mentoring process, drawing from theory and research on child and adolescent development and close relationships. Although we view the processes outlined in this model as generally applicable to mentoring relationships in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
294
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(321 citation statements)
references
References 54 publications
17
294
1
9
Order By: Relevance
“…Similarly, longitudinal research has shown the benefit of having a natural mentor in adolescence for predicting optimism in later adolescence (Kogan, Brody & Chen, 2011) as well as life satisfaction and psychological well-being in young adulthood (Hurd & Zimmerman, 2014). Mentors offer support and care, which can help adolescents develop a more positive self-concept and in turn lead to better psychological functioning (Rhodes, Spencer, Keller, Liang & Noam, 2006). Mentors can also model emotion regulation and provide opportunities to develop these skills.…”
Section: Psychological Well-beingmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, longitudinal research has shown the benefit of having a natural mentor in adolescence for predicting optimism in later adolescence (Kogan, Brody & Chen, 2011) as well as life satisfaction and psychological well-being in young adulthood (Hurd & Zimmerman, 2014). Mentors offer support and care, which can help adolescents develop a more positive self-concept and in turn lead to better psychological functioning (Rhodes, Spencer, Keller, Liang & Noam, 2006). Mentors can also model emotion regulation and provide opportunities to develop these skills.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…Mentors provide adolescents with opportunities to learn new strategies such as positive ways of responding and behaving in social situations and emotion regulation skills (Rhodes et al, 2006). These skills are predictive of relationship satisfaction in adulthood (Bradbury & Scaffer, 2012;Malouff, Schutte & Thorsteinsson, 2014).…”
Section: Romantic Relationship Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably one of the most critical mentoring processes for the preservation of healthy MRs is relationship quality. Rhodes, Spencer, Keller, Liang and Noam (2006) assert that feelings of closeness and warmth between the mentor and mentee lie at the heart of the MR and must be solidified for mentoring to make a noticeable impact in the lives of youth. In their view, relationships that do not have these qualities are doomed for failure (Rhodes et al, 2006).…”
Section: Correlates Of Mr Closuresmentioning
confidence: 99%